Applications of mu c-SiOx:H as integrated n-layer and back transparent conductive oxide for a-Si:H/mu c-Si:H tandem cells - Liang, Shin-Wei; Huang, Yen-Tang; Hsu, Hung-Jung; Hsu, Cheng-Hang; Tsai, Chuang-Chuang (My University, 2014)
We have prepared n-type hydrogenated microcrystalline silicon oxide [mu c-SiOx:H(n)] films with oxygen contents from 0 to 37.3 at. % by varying the CO2-to-SiH4 flow ratio in a plasma-enhanced chemical vapor deposition (PECVD) system. By using mu c-SiOx:H(n) as an effective replacement for integrated mu c-Si:H(n) and indium-tin oxide (ITO), mu c-Si:H single-junction and a-Si:H/mu c-Si:H tandem cells exhibited significantly improved efficiencies of 6.35 and 10.53%, respectively. The improvement of the single-junction and tandem cells mainly arose from the enhancement of long-wavelength optical absorption in mu c-Si:H absorbers, which was confirmed by a quantum efficiency instrument showing a markedly enhanced spectral response at wavelengths from 600 to 1100 nm. Moreover, all the PECVD processes, except the metal contact, had an advantage of in situ deposition without breaking vacuum, thereby minimizing contamination of the interface. The simplified cell fabrication can enhance the fill factor, which will benefit industrial production. (C) 2014 The Japan Society of Applied Physics